Answer:
[tex]f^{-1}(x)=\pm\sqrt{x-16}[/tex]
Step-by-step explanation:
The given equation is [tex]y=x^2+16[/tex]
Interchange the positions of x and y
[tex]x=y^2+16[/tex]
Now, solve this equation for y. That would be the inverse of this function.
Subtract 16 to both sides of the equation
[tex]x-16=y^2[/tex]
Take square root both sides
[tex]y=\pm\sqrt{x-16}[/tex]
This is the inverse of the given function.
[tex]f^{-1}(x)=\pm\sqrt{x-16}[/tex]
Answer:
if the person above is right its C on ed.
Step-by-step explanation:
i read the answer above